Veterans Treatment Courts: An Exploratory Analysis of the Effect of Veteran Mentors - Gerhardt, T. Freeman (Criminal justice policy review, 2023)
Few studies have investigated the effect of mentorship on participants’ clinical or criminal justice outcomes in veterans treatment courts (VTCs). This study is an exploratory analysis of a VTC in Hillsborough County, Florida. Descriptive and inferential statistics were used to examine behavioral health changes between baseline and follow-up and compare participants with/without a mentor. Post hoc analyses explored the effect of mentorship on graduation and re-arrest rates. Participants with a mentor had significant improvements in mental health, trauma, substance use, and social support; and significantly higher levels of positive social interaction than those without a mentor. Mentor status was not meaningfully related to graduation and re-arrest rates in bivariate analyses, but post hoc analyses found that social support mediated the relationship between mentor satisfaction and re-arrest and graduation rates.